2016
DOI: 10.1128/aem.03861-15
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Involvement of Fenton Chemistry in Death of Methicillin-Resistant and Methicillin-Sensitive Strains of Staphylococcus aureus and Destruction of Their Genomes on Wet or Dry Copper Alloy Surfaces

Abstract: The pandemic of hospital-acquired infections caused by methicillin-resistant Staphylococcus aureus (MRSA) has declined, but the evolution of strains with enhanced virulence and toxins and the increase of community-associated infections are still a threat. In previous studies, 10 7 MRSA bacteria applied as simulated droplet contamination were killed on copper and brass surfaces within 90 min. However, contamination of surfaces is often via finger tips and dries rapidly, and it may be overlooked by cleaning regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 23 publications
5
30
0
Order By: Relevance
“…Studies have suggested that both lipid peroxidation and cell death occur before genomic DNA degradation, but in some cases genomic DNA is not degraded during the course of cell death (14,22). This finding indicates that genomic DNA degradation is not the main cause of cell death (14) but may play a role in preventing the horizontal transfer of antibiotic resistance genes in other organisms (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that both lipid peroxidation and cell death occur before genomic DNA degradation, but in some cases genomic DNA is not degraded during the course of cell death (14,22). This finding indicates that genomic DNA degradation is not the main cause of cell death (14) but may play a role in preventing the horizontal transfer of antibiotic resistance genes in other organisms (13).…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, more than 300 copper surfaces were registered by the Environmental Protection Agency as antimicrobial materials (12). Studies have confirmed that contact with copper surfaces kills Staphylococcus aureus, Escherichia coli, and most other bacteria within hours or even seconds, due to the combinatory effects of copper-ion-induced reactive oxygen species (ROS) generation (13), lipid peroxidation (14), damage to cell membrane integrity (15), DNA degradation (16), aberrant protein expression (17), inactivation of metalloproteins (18), and other factors. In marine fish farming, copper is used for corrosion-resistant cages, and copper coating is also used for its anticorrosive, antibacterial, and antiadhesive properties (19).…”
mentioning
confidence: 99%
“…The longer a bacterium persists on a surface, the greater the opportunity to be spread [ 4 ]. Therefore, rapid decontamination times will decrease the chance that bacteria may be transferred to a new surface before sterilisation is achieved, and will decrease the likelihood of resistance developing [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Studies have found that copper surfaces rapidly reduce bacterial loads through a process known as contact killing against both gram-positive and gram-negative bacteria. [13][14][15][16][17] With the rise of antibiotic-resistant bacteria, such as MRSA, the use of copper alloy surfaces provides a mean of not only reducing bacterial burden, but also mitigating the spread of antibiotic-resistant bacteria in the environment. The implementation of copper alloys on high-touch surfaces in the hospital resulted in decreased bacterial counts on surfaces in comparison with control surfaces.…”
mentioning
confidence: 99%